1998
DOI: 10.1136/oem.55.4.258
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms and bronchial responsiveness in lifeguards exposed to nitrogen trichloride in indoor swimming pools.

Abstract: Objectives-To measure the levels of exposure to nitrogen trichloride (NCl 3 ) in the atmosphere of indoor swimming pools and to examine how they relate to irritant and chronic respiratory symptoms, indices of pulmonary function, and bronchial hyperresponsiveness to methacholine in lifeguards working in the pools. Method-334 lifeguards (256 men; 78 women) recruited from 46 public swimming pools (n=228) and 17 leisure centre swimming pools (n=106) were examined. Concentrations of NCl 3 were measured with area sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
142
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(164 citation statements)
references
References 17 publications
(5 reference statements)
13
142
0
9
Order By: Relevance
“…Measured chloramine levels in the present study exceeded this comfort level regularly. MASSIN et al [3] found average concentrations of 0.67 mg?m -3 chloramine in leisure pools, which are of the same magnitude as present findings, and 0.24 mg?m -3 chloramine in public pools. HERY et al [4] found approximately similar values (0.64 and 0.27 mg?m -3 , respectively).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Measured chloramine levels in the present study exceeded this comfort level regularly. MASSIN et al [3] found average concentrations of 0.67 mg?m -3 chloramine in leisure pools, which are of the same magnitude as present findings, and 0.24 mg?m -3 chloramine in public pools. HERY et al [4] found approximately similar values (0.64 and 0.27 mg?m -3 , respectively).…”
Section: Discussionsupporting
confidence: 79%
“…MASSIN et al [3] studied the relationship between trichloramine air levels and irritant and chronic respiratory symptoms, indices of lung function and bronchial hyperresponsiveness (BHR) in 334 French lifeguards. No associations were found between exposure and BHR, chronic bronchitis and asthma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NCl 3 is suspected to be responsible for the appearance of asthma to swimmers, swimming teachers and lifeguards (Thickett et al, 2002) and to cause eye, nasal and throat irritations (Massin et al, 1998;Thickett et al, 2002). NCl 3 is a compound with low solubility in water; it is four times more volatile than chloroform and has a penetrating odor, which makes it one of the most important air pollutants of indoor pools (Schmalz et al, 2011).…”
Section: Trichloraminementioning
confidence: 99%
“…The chloramines and bromamines, particularly nitrogen trichloride and nitrogen tribromide, which are both volatile (Holzwarth et al, 1984), can give rise to signifi cant eye and respiratory irritation in swimmers and pool attendants (Massin et al, 1998). In addition, nitrogen trichloride has an intense and unpleasant odour at concentrations in water as low as 0.02 mg/l (Kirk & Othmer, 1993).…”
Section: Risks Associated With Disinfection By-productsmentioning
confidence: 99%